Wire-mesh inhibition of jet fire induced by explosion venting. (May 2021) - Wang, Zhirong; Lu, Yawei; Cao, Xingyan; Yu, Yuan; Jiang, Juncheng; Jiao, Fei; Ma, Shichang
Abstract: Explosion venting is widely applied in industrial explosion-proof designs due to the convenient, economical and practical features of this method. Natural gas is usually stored in storage tanks. If the gas in the vessel is mixed with air and encounters an ignition source, explosion venting might occur, producing jet fire, generating new secondary derivative accidents and causing casualties and property losses. In this paper, a set of test platforms including wire-mesh suppression devices is established to study the inhibition of jet fire induced by explosion venting by wire mesh. The experimental research shows that a wire mesh significantly inhibits the jet fire induced by explosion venting. The flame propagation velocity and pressure clearly decrease with increasing numbers of wire-mesh layers. The wire-mesh structure significantly affects the flame propagation, and the more layers of mesh there are, the better the suppression effect is. The flame temperature gradually decreases with the addition of the wire mesh. The mesh size significantly affects the pressure propagation of explosion venting. The explosion pressure gradually decreases with the addition of the wire mesh. With increasing distance between the wire mesh and the explosion vent, the maximum temperature first increases and then decreases, and the maximum explosion pressure first decreases and then increases. In the case of single gas cloud, the flame suppression effect is the most obvious when the wire mesh is 0.2 m away from the explosion vent. In the case of double gas clouds, the flame suppression effect is the most significant when the distance between the wire mesh and the first gas cloud is 0.4 m. Highlights: As the number of mesh layers and the mesh size increase, the venting pressure decreases. As the number of mesh layers and size increase, the strength of the flame weakens, and the flame propagation speed reduces. As the number of mesh layers and mesh size increase, the temperature of the external environment of the wire mesh decreases. With increasing distance from the mesh to the venting port, the venting pressure first decreases and then increases.